Comprehensive Teaching Materials Based on Cognitive Conflict Strategies to Reduce Misconception of Calories for Junior High School Students - Heny Ekawati Haryono; Khafidhoh Nurul Aini; Achmad Samsudin; Parsaoran Siahaan (Universitas Muhammadiyah Makassar, 2021)
Heat is a material that is close to everyday life. However, most students still have misconceptions about this material. Thus, teachers need to develop teaching materials that can reduce the misconception of heat material. One alternative is to use teaching materials with cognitive conflict strategies. The research aims to develop teaching materials that are able to reduce students' misconceptions about heat material. The development model used is the 4D model which consists of four stages, namely defining, designing, developing, and distributing. The teaching materials developed include lesson plans, textbooks, student worksheets, and tests. The subjects of the study were seventh-grade students in Lamongan regency which consisted of 10 state junior high schools and private junior high schools. The research instrument was a feasibility test sheet for teaching materials and a questionnaire to see students’ responses. Data collection techniques used the feasibility sheet of teaching materials and questionnaires. Therefore, the result shows that cognitive conflict-based teaching materials are appropriate to be used classroom with a score between 3.0 and 3.9 and a reliability coefficient value of more than 90%. and can reduce misconceptions with a percentage reduction in misunderstandings from 10 junior high schools in the Lamongan regency ranging from 30.3 to 47.8 percent.